Criminal Sanctions for Perpetrators of Human Trafficking in Indonesia - Samsidar, Samsidar (PT. Anagata Sembagi Education, 2025)
Human trafficking is a serious crime that violates human rights and threatens the dignity of victims, especially in Indonesia, which is a source, transit, and destination country. This crime not only harms individual victims physically and psychologically, but also has a negative impact on national social and economic development. Indonesia has strictly regulated human trafficking in Law Number 21 of 2007 concerning the Eradication of the Crime of Human Trafficking (UU TPPO) along with the Criminal Code and other supporting regulations. This article aims to analyze the application of criminal sanctions against perpetrators of human trafficking in Indonesia and the challenges in enforcing them. The normative legal method is used to examine the relevant regulations and court decisions. The results of the study indicate that the criminal sanctions applied are quite severe normatively, but in practice there are still obstacles in the form of lack of coordination between institutions, minimal protection for victims, and suboptimal law enforcement. Recommendations are given so that strengthening the legal system and a multidisciplinary approach can improve the effectiveness of handling human trafficking in Indonesia.